American apostles when evangelicals entered the world of Islam - Heyrman, Christine Leigh (Hill and Wang, a division of Farrar, Straus and Giroux, 2015)
In "American Apostles," the Bancroft Prize-winning historian Christine Leigh Heyrman brilliantly chronicles the first fateful collision between American missionaries and the diverse religious cultures of the Levant. The political and religious consequences of that outcome endure to this day.